Optimization Of The Online Permit Service System For Community Organizations: Case Study Of Dpm-Ptsp South Sulawesi Province - Indriati Amirullah; Nurasia Natsir (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to optimize the online permit service system for community organizations at the South Sulawesi Province One-Stop Integrated Licensing and Investment Service (DPM-PTSP). In its implementation, this system faces several problems that can affect the efficiency and effectiveness of services. Through qualitative research methods, this research tries to identify and analyze these problems and offer possible solutions. Data was collected through interviews, observation and documentation studies. The research results show that some of the main problems include technical problems, lack of digital literacy among users, and lack of coordination between departments. Based on these findings, this research suggests several strategies to optimize this online permit service system, including improving technological infrastructure, digital training programs, and improving coordination between departments. This research is likely to contribute to improving the quality of online permit services in the DPM-PTSP of South Sulawesi Province and other areas with similar conditions.